Ethnographic Study of Sasak Language and Culture as Local Wisdom in SDGs to Preserve Sustainability Knowledge and Noble Traditions - Rabiyatul Adawiyah (Universitas Pendidikan Mandalika, 2026)
Pamali is a form of local wisdom that has been passed down from generation to generation and is still believed by some people today. Pamali reflects prohibitions or warnings that are believed to bring bad luck if violated. The purpose of this study is to determine the realization of Pamali words in Sasak culture as expressions and usage in pronouns, as well as the cultural values of Pamali words, and to describe Pamali in supporting the sustainability of knowledge and noble traditions within the framework of SDGs. This study is based on linguistic anthropology and ethnography theories. Data in this study were collected by applying participatory observation and in-depth interview methods, accompanied by recording and note-taking techniques. The data were analyzed using two methods: the Miles and Haberman analysis model (data collection, data reduction, data presentation, and conclusion) and the Spradley analysis model. The results of the analysis show that the Sasak people view pamali as a norm that, if upheld, can create peace and tranquility in life; conversely, if violated, it can lead to dehumanization. The word pamali is practiced by the Sasak people in the form of greetings, which are used in the form of nouns and are closely related to cultural and ethical norms. Pamali in Sasak society serves to regulate politeness and maintain social harmony through pronouns that are sensitive to age and status, where violations are considered to be a violation of honor. This practice also preserves cultural knowledge and supports the sustainability of local traditions within the framework of the SDGs.